A escuta de histórias de violência doméstica : da busca do amor ao encontro com a dor - Mendonça, Jackeline Jardim (2020)
This dissertation is the product of research carried out in the Graduate Program in Psychology (PPGPsi) at the Federal University of Mato Grosso - UFMT and is part of the Clinical Processes and Sociocultural Contexts Research Line. The situations of violence by which many women are victimized during their social life can generate debates. Public policy and Brazilian legislation contribute to tackling these practices of gender-based violence, but it is known that many women are still unable to leave violent relationships and, for this reason, the researcher asked the following question to start this research: What are the unconscious determinants of this painful situation, which does not stop happening? How has a cycle of domestic violence been structured in the lives of some women? How do you relate to companions and more violent companions? It presents the research carried out with women in shelter at the Casa de Amparo à Mulher Vítima de Violência in the city of Cuiabá-MT. The survey data collection took place in the second half of 2018. Two women who were at the institution during this period participated. Because it is a theme where debates of a socio cultural and psychological nature occur, since subjectivity here is understood from Psychoanalysis, considering the subject of the unconscious, an unconscious that is transindividual, we are invited to articulate our discussions around these two fields, psyche and culture / society. The first part of this work corresponds to sections I and II that present the socio-cultural field of the subjective constitution of women in Western culture and the Brazilian socio-political context of guaranteeing women's rights. The other part, on the other hand, presents research in psychoanalysis and possible interpretations of women's history. Occasionally, Section I presents how, when dealing with violence against women, it became essential to present questions about gender and patriarchy, also making an intersection between gender, race and class. Based on authors from different areas of knowledge, it elucidates how the condition of subordination of women is socially and culturally constructed due to gender hierarchy. Section II discusses the struggle path of social and, finally, political movements that enabled the elaboration of specific legislation to face violence against women (Law nº 11.340 / 2016 - Lei Maria da Penha).The way in which public policies are currently in order to tackle these violence is also presented, in this context the presentation of the Casa de Amparo a Mulher Vítima de Violência in Cuiabá is included. Section III presents the methodological path taken by the researcher in carrying out this research. Finally, Section IV presents the results and discussions of the collected data. We can glimpse the primary relationships of Maria and Marielle, women victims of domestic violence who were welcomed at Casa de Amparo. The interpretations of these participants' interviews do not lead to debate family relationships, how the maternal and paternal micro institutions are embodied in the psyche. These women participated in unstructured interviews where they were asked to speak whatever came to mind about the relationships that led them to Casa de Amparo, in these interviews, in addition to dealing with the love present in the loving relationships with the partners, we came across what resulted in these relationships, the fundamental love, the constitutive love of primary relationships, originating in families and which, as understood, impact on social and loving relationships. Thus,as primary, family relationships, they are fundamentally constitutive of the ways of relating to friends in the future, in addition to being carried out by the internalization of culture and thus, the repetitions of the subordination of the female gender and all the naturalized inequalities with which women coexist.